Aminophylline Induced Blood Pressure Decrease in Patients with Acute Phase Non-Hemorrhagic Stroke and Chronic Obstrutive Pulmonary Disease (COPD) - Sahil Haikal, Sayyid Muhammad; Dirgantara Putra, Aryo (Jurnal Kedokteran Brawijaya, 2025)
Stroke and Chronic Obstrutive Pulmonary Disease (COPD) are two diseases that have high mortality and disability rates in the world. Smoking is one of the risk factors that cause these two diseases. The occurrence of Non-Hemorrhagic Stroke (NHS) and COPD simultaneously in one patient will cause a poor prognosis and more comprehensive treatment. In addition, there are no therapeutic guidelines for these two diseases if they occur together. This case report reports a case of NHS and COPD in a 64-year-old man who received aminophylline therapy. The patient experienced hypotension on the second day of treatment induced by aminophylline administration. Discontinuation of aminophylline therapy in the patient and administration of other supportive therapies for NHS and COPD showed improvements in blood pressure and other medical conditions related to the patient's disease on the sixth day of treatment. A decrease in blood pressure by >15% in the acute phase of NHS is a quite dangerous condition because it causes a lack of collateral blood flow which results in a lack of blood flow in the penumbra area. Administration of aminophylline has the effect of lowering blood pressure because it increases the release of catecholamines that stimulate beta adrenergic to reduce vascular resistance. Aminophylline should be given >48 hours after the attack to prevent the expansion of cerebral infarction and recurrent NHS attacks and strict monitoring is required when administering COPD therapy accompanied by NHS in relation to the effects caused by the administration of this therapy.